2017
DOI: 10.1155/2017/2435079
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Influence of the Penetration Channel’s Shape on Plasma Parameters When Handling Highly Concentrated Energy Sources

Abstract: In our work to formulate a scientific justification for process control methods when processing materials using concentrated energy sources, we develop a model that can calculate plasma parameters and the magnitude of the secondary waveform of a current from a non-self-sustained discharge in plasma as a function of the geometry of the penetration channel, thermal fields, and the beam's position within the penetration channel. We present the method and a numeric implementation whose first stage involves the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Liu and Wu have studied the dynamic behavior of keyhole which can determine the weld quality to achieve strong welded metal joint [2,3]. Kuril and Trushnikov have shown that keyhole in the PAW depends on the welding condition, such as welding current, pilot gas and welding speed [4,5]. Li have simulated the influence of welding parameters in PAW.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Wu have studied the dynamic behavior of keyhole which can determine the weld quality to achieve strong welded metal joint [2,3]. Kuril and Trushnikov have shown that keyhole in the PAW depends on the welding condition, such as welding current, pilot gas and welding speed [4,5]. Li have simulated the influence of welding parameters in PAW.…”
Section: Introductionmentioning
confidence: 99%